2015
DOI: 10.3389/fenvs.2015.00008
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical analysis of ancient Pacific Cod bone suggests Hg bioaccumulation was linked to paleo sea level rise and climate change

Abstract: Deglaciation at the end of the Pleistocene initiated major changes in ocean circulation and distribution. Within a brief geological time, large areas of land were inundated by sea-level rise and today global sea level is 120 m above its minimum stand during the last glacial maximum. This was the era of modern sea shelf formation; climate change caused coastal plain flooding and created broad continental shelves with innumerable consequences to marine and terrestrial ecosystems and human populations. In Alaska,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 37 publications
1
10
0
1
Order By: Relevance
“…Diagenesis refers to changes in the chemical constituent of tissue after deposition in sediments, which is always a concern in trace element and stable isotope analysis of archeological bone. However, previous studies have provided results on the level of mercury in bones or other biological remains (hair) of animal species (fish and mammals) from different archeological periods (Emslie et al, 2019; Gerlach et al, 2006; Halffman, 2009; Murray et al, 2015) and have demonstrated the reliability of mercury measurement and its biogenic origin. These authors mention that it is unlikely that the Hg levels in the remains would be affected by diagenesis, either by a decline or intrusion, especially because the concentration ranges are similar between ancient and modern samples.…”
Section: Discussionmentioning
confidence: 99%
“…Diagenesis refers to changes in the chemical constituent of tissue after deposition in sediments, which is always a concern in trace element and stable isotope analysis of archeological bone. However, previous studies have provided results on the level of mercury in bones or other biological remains (hair) of animal species (fish and mammals) from different archeological periods (Emslie et al, 2019; Gerlach et al, 2006; Halffman, 2009; Murray et al, 2015) and have demonstrated the reliability of mercury measurement and its biogenic origin. These authors mention that it is unlikely that the Hg levels in the remains would be affected by diagenesis, either by a decline or intrusion, especially because the concentration ranges are similar between ancient and modern samples.…”
Section: Discussionmentioning
confidence: 99%
“…In the North Atlantic, which has declining mercury concentrations in water in response to environmental regulations in North America and Europe, Cross et al and Lee et al documented declines in mercury concentrations of bluefish ( Pomatomus saltatrix ) and Atlantic bluefin tuna ( Thunnus thynnus ), respectively, captured from the Northwest Atlantic coast. Over the past 6000 yr, mercury concentrations in bones of Pacific cod ( Gadus macrocephalus ; recovered from a small island in the Gulf of Alaska) have fluctuated in sync with climate changes , with the highest concentrations occurring when glacial melting and sea‐level rise caused coastal flooding that is speculated to have increased the flux of mercury and methylmercury from land to water. In the modern record for the North Pacific, where mercury concentrations in water are increasing as a result of export of atmospheric mercury from Asia , increasing trends of mercury concentrations have also been observed in yellowfin tuna ( Thunnus albacares ) and in black‐footed albatross ( Phoebastria nigripes ) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, environmental pollution by means of mercury may result in human diseases (Harada 1995). An increased mercury content was described from historic human bone remains (Yamada et al 1995, Rasmussen et al 2008 and in a Pleistocene Pacific cod (Murray et al 2015), but not in older fossils. Therefore, the bioaccumulation and biomagnification processes may potentially be considered as a possible origin of such a significant amount of mercury in the examined fossil material.…”
Section: Discussionmentioning
confidence: 99%